Linkage refinement localises Sorsby fundus dystrophy between markers D22S275 and D22S278. Issue 3 (March 1995) - Gregory, C Y; Wijesuriya, S; Evans, K; Jay, M; Bird, A C; Bhattacharya, S S
Abstract : Sorsby fundus dystrophy is an autosomal dominant disorder which both clinically and histopathologically bears striking similarities to age related macular degeneration, one of the leading causes of blindness in the developed world. Recent studies have suggested a genetic localisation of the disease to chromosome 22q in a large genetic interval of approximately 25 cM. Independent genetic linkage analysis in a six generation British pedigree confirms linkage to the chromosome 22q region. A maximum two point lod score of 7.09 with no recombination was obtained with marker D22S280. Haplotype data positioned the disease between loci D22S275 and D22S278, thus significantly reducing the region on chromosome 22q where the gene is located.